Multiculturalism Obscured: Paris Museum Cultures and the Musée de l'Institut du monde arabe. Issue 2 (July 2019) - King, Gemma
Abstract : Since the transformation of the Louvre from royal atelier to Republican museum in 1793, French museums have played an important role in reinforcing ideas about the place of France in the world, and defining its relationship with its others. However, many Paris museums struggle to represent, confront or express the full complexity of France's colonial past, its multicultural population and its place on the world stage in a postcolonial era of immigration and globalization. This article explores how Parisian "ethnological" museums, from the Palais de la Porte Dorée to the Musée du Quai Branly, struggle to represent these truths. It then focuses in on the Musée de l'Institut du monde arabe, and how this museum mostly fails to portray the interlaced and even inseparable histories of the Arabophone and Francophone worlds. Instead, the museum's representation of the "Arab World" favours a discourse of cultural separatism which is at odds with the multicultural reality of the contemporary French population, and ignores the linguistic and cultural ecologies of the many former French colonies across North Africa that comprise a large proportion of the "Arab World" itself.